Deontological Competence and Its Role in Sports Education - Hamrayev Bakhtiyor (Zamonaviy ilmiy yondashuvlar va texnologik taraqqiyotning ustuvor yo‘nalishlari, 2026)
This article analyzes the role and importance of deontological competence in sports education. The article examines the main elements of deontological competence, its role in the activities of athletes, coaches and other sports professionals. It also discusses how deontological competence affects the personal and physical development of athletes in the process of sports education, as well as its importance in improving the social environment. The benefits of developing deontological competence in sports education and how it contributes to the success of athletes are discussed in detail.